2018
DOI: 10.1080/00224545.2018.1477442
|View full text |Cite
|
Sign up to set email alerts
|

Empathy present and future

Abstract: The empathy concept has central significance for social and personality psychology and in many other domains, including neuroscience, clinical/abnormal psychology, and the health professions. However, the current diversity in conceptual and operational definitions, and the promiscuous use of the term "empathy," threaten the ability of researchers to advance the field. The present article provides a quantitative review and conceptual analysis of empathy definitions and usages by examining 393 studies published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
199
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 100 publications
5
199
0
13
Order By: Relevance
“…In contemporary scientific approach, empathy is the major topic of social, developmental, and personality psychology as well as other disciplines, such as neuroscience, clinical psychology, psychotherapy, and various health professions [47]. Empathy is very complex and multidimensional phenomenon.…”
Section: A Contemporary Approach To Defining Empathymentioning
confidence: 99%
See 4 more Smart Citations
“…In contemporary scientific approach, empathy is the major topic of social, developmental, and personality psychology as well as other disciplines, such as neuroscience, clinical psychology, psychotherapy, and various health professions [47]. Empathy is very complex and multidimensional phenomenon.…”
Section: A Contemporary Approach To Defining Empathymentioning
confidence: 99%
“…The important quantitative review and conceptual analysis of empathy gave Hall and Schwartz [47] which used random selection method to analyze 393 studies published between 2001 and 2013, and 96 studies published in 2017. They found that empathy is most commonly seen as a multidimensional concept divisible into dimensions, facets, factors, types, subscales, substrates, processes, aspects, etc.…”
Section: A Contemporary Approach To Defining Empathymentioning
confidence: 99%
See 3 more Smart Citations